2016
DOI: 10.1038/srep33666
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of periodontitis-associated fibroblasts by CAGE sequencing identified DLX5 and RUNX2 long variant as novel regulators involved in periodontitis

Abstract: Periodontitis is affecting over half of the adult population, and represents a major public health problem. Previously, we isolated a subset of gingival fibroblasts (GFs) from periodontitis patients, designated as periodontitis-associated fibroblasts (PAFs), which were highly capable of collagen degradation. To elucidate their molecular profiles, GFs isolated form healthy and periodontitis-affected gingival tissues were analyzed by CAGE-seq and integrated with the FANTOM5 atlas. GFs from healthy gingival tissu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 51 publications
0
30
0
1
Order By: Relevance
“…18 Human fibroblasts have also been analyzed in transcriptomic studies of periodontitis, providing a more comprehensive overview of periodontitis-related fibroblast transcriptomes. 11…”
Section: Tr Anscrip Tomic Smentioning
confidence: 99%
“…18 Human fibroblasts have also been analyzed in transcriptomic studies of periodontitis, providing a more comprehensive overview of periodontitis-related fibroblast transcriptomes. 11…”
Section: Tr Anscrip Tomic Smentioning
confidence: 99%
“…Naturally, mutations affecting the function of these transcription factors would affect the integrity of the ECM by altering its composition. Most of the transcription factors included on the list fall in this category, often regulating directly the expression of collagen, fibronectin, or cadherin genes (Bi et al, ; Hsieh et al, ; Cho et al, ; Papangeli and Scambler, ; Simental‐Mendia et al, ; Horie et al, ; Yoh et al, ). Transcriptional control might be contextual as seen with the Saethre–Chotzen gene TWIST1 (101400) that can both upregulate and downregulate collagen expression (Fang et al, ; Garcia‐Palmero et al, ).…”
Section: Ecm Expression During Palatal Growthmentioning
confidence: 99%
“…It was reported that GF cultured in osteogenic media differentiated into osteoblasts . An appropriate ECM signal can direct GF to form hard tissue through expression of mRNA for alkaline phosphatase and bone morphogenetic protein 2/4 (BMP2/4) . In addition, it has been reported that each fibroblast culture contains a small proportion of mesenchymal stem cells (MSCs) without undergoing an enrichment selection procedure .…”
Section: Discussionmentioning
confidence: 99%